Aprovechamiento de la energía eólica mediante el diseño, construcción e implementación de un generador eólico en una vivienda ubicada en el barrio La Florida, cantón Salcedo, provincia de Cotopaxi en el periodo 2013 – 2014 - Cepeda Paredes, William Eduardo (2015)
This research pretends to develop a wind turbine design. It lets to use the wind resource in an efficient way. This action consists the recycled materials use. It avoids to become environmental liabilities. In other words, it contributes to take care the environment since two sides. In the design as a fundamental part of weight reduction of the structure to decrease the wind inertia must be overcome to start the power generation. In addition, it looks for a more modern and compact design that allows the use of wind energy more efficiently. This saves time and resources. Using design software experimentation 3 dimensional construction avoided. So, it allows evaluating premature failure of the system. It generates more than the plans for their prototype construction….